Association Between Epicardial Adipose Tissue and Stroke - Rosa, Maria Inês; Grande, Antonio José; Lima, Leticia Dorsa; Dondossola, Eduardo Ronconi; Uggioni, Maria Laura Rodrigues; Hernandez, Adrian V.; Tse, Gary; Liu, Tong; Pontes-Neto, Octávio Marques; Biondi-Zoccai, Giuseppe; Neto, Mansueto Gomes; Durães, André Rodrigues; et al. (Frontiers in Cardiovascular Medicine, 2021)
Epicardial adipose tissue (EAT) is correlated with endothelial dysfunction, metabolic syndrome, increased mortality and recent studies showed a possible association with the increased risk of stroke. We performed a systematic review of studies evaluating the association between EAT and stroke. Eighty studies met the inclusion criteria and were consequently analyzed. The review had Five main findings. First, the increased epicardial fat thickness (EFT) may be associated with the stroke episode. Second, regardless of the imaging method (echocardiography, MRI, and CT) this association remains. Third, the association of metabolic syndrome and atrial fibrillation seems to increase the risk of stroke. Fourth, the association with risk factors may be involved in increasing this risk. Fifth, this systematic review was considered as low risk of bias. Despite being unable to establish a clear association between EAT and stroke, we have organized and assessed all the research papers on this topic, analyzing their limitations, suggesting improvements in future pieces of research and pointing out gaps in the literature. Furthermore, the mechanistic links between increased EAT and stroke incidence remains unclear, thus, further research is warranted.